2017
DOI: 10.1111/jnc.13991
|View full text |Cite
|
Sign up to set email alerts
|

IP3 receptor mutations and brain diseases in human and rodents

Abstract: The inositol 1,4,5-trisphosphate receptor (IP 3 R) is a huge Ca 2+ channel that is localized at the endoplasmic reticulum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 227 publications
(402 reference statements)
3
48
0
Order By: Relevance
“…Deregulation of calcium signaling in neurons may also play a role in the pathogenesis of SCA types 15/16 and 29 (SCA15/16 and SCA29), Gillespie's syndrome, sensory ataxia and some other neurodegenerative disorders (Table 1). These data indicated that IICR might be one of the causes of pathophysiological events in neuronal cells [7,8].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Deregulation of calcium signaling in neurons may also play a role in the pathogenesis of SCA types 15/16 and 29 (SCA15/16 and SCA29), Gillespie's syndrome, sensory ataxia and some other neurodegenerative disorders (Table 1). These data indicated that IICR might be one of the causes of pathophysiological events in neuronal cells [7,8].…”
Section: Introductionmentioning
confidence: 75%
“…The three genes that encode the three IP 3 R subtypes, IP 3 R1, IP 3 R2 and IP 3 R3, have been identified and cloned in mammalian cells [15]. The expression of different IP 3 R subtypes is cell type-dependent [8,16]; for example, cerebellar PCs mainly express IP 3 R1, insulin-secreting b-cells express IP 3 R3 [17] and cardiac myocytes express predominantly IP 3 R2 [18]. The IP 3 R1 isoform is observed predominantly in central nervous system neurons, but most other tissues express at least two and often all three IP 3 R isoforms at different ratios.…”
Section: Identification Of Ip 3 Rsmentioning
confidence: 99%
“…The subunits are enormous (∼2700 residues), such that IP 3 Rs and RyRs (which are even larger, 4 × ∼5000 residues/RyR) are the largest known ion channels. The IP 3 R subtypes differ in their patterns of expression between tissues ) and perhaps in their subcellular distributions (Vervloessem et al 2015), they have different affinities for IP 3 (IP 3 R2 > IP 3 R1 > IP 3 R3) (Iwai et al 2007), they differ in their associations with other proteins and in their modulation by additional signals (Prole and Taylor 2016), they appear to differ in their capacity to sustain oscillatory Ca 2+ signals (Miyakawa et al 1999;Wang and Yule 2018), and the functional consequences of perturbing IP 3 Rs differ for the different subtypes (Hisatsune and Mikoshiba 2017). Despite the differences, the core functional properties of all IP 3 Rs are similar and so too are their structures, consistent with the sequence conservation (∼70%) between subtypes (Fan et al 2015(Fan et al , 2018Paknejad and Hite 2018).…”
Section: Ip 3 Receptors Are Regulated By Ip 3 and Ca 2+mentioning
confidence: 99%
“…Modulatory proteins also provide links between IP 3 Rs and human diseases, additional to those arising from loss or mutation of IP 3 Rs (Berridge 2016;Casey et al 2017;Hisatsune and Mikoshiba 2017;Terry et al 2018). The mutant forms of Huntingtin associated with Huntington's disease, mutant ataxins associated with spinocerebellar ataxias, and mutant presenilins associated with inherited forms of Alzheimer's disease, for example, have each been reported to enhance IP 3 -evoked Ca 2+ signals (Chen et al 2008;Cheung et al 2008Cheung et al , 2010Liu et al 2009;Egorova and Bezprozvanny 2018).…”
Section: Ip 3 Receptors As Signaling Hubsmentioning
confidence: 99%
See 1 more Smart Citation